2017
DOI: 10.1016/j.ijbiomac.2017.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial shear rheology of β-lactoglobulin—Bovine submaxillary mucin layers adsorbed at air/water interface

Abstract: The interfacial rheological properties of solutions of β-lactoglobulin (BLG), as a model food compound, mixed with bovine submaxillary mucin (BSM), a major salivary protein, have been investigated. Time, frequency, stress sweep and flow measurements have been performed at different pHs (7.4, 5.0 and 3.0), to investigate the air/water interfacial properties. All protein layers (BLG, BSM, and BLG-BSM mixtures) formed an elastic network at the air/water interface with low frequency dependence of the interfacial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The whey globular protein β-lactoglobulin (BLG) is frequently used as a model protein in foam and interfacial studies. Adsorption dynamics and surface rheology of native BLG layers at static water/air interfaces [8,25,[35][36][37][38][56][57][58][59][60], as well as foam film thickness [25,61], have been previously studied as affected by pH. It was proven by vibrational sum-frequency generation (SFG) spectroscopy that the pH-dependent net charge of BLG in solution determines the magnitude of the electric field at the solution's interface and thereof, a charge reversal can occur when the isoelectric point of BLG moieties (pI ≈ 5.1) is crossed [35].…”
Section: Introductionmentioning
confidence: 99%
“…The whey globular protein β-lactoglobulin (BLG) is frequently used as a model protein in foam and interfacial studies. Adsorption dynamics and surface rheology of native BLG layers at static water/air interfaces [8,25,[35][36][37][38][56][57][58][59][60], as well as foam film thickness [25,61], have been previously studied as affected by pH. It was proven by vibrational sum-frequency generation (SFG) spectroscopy that the pH-dependent net charge of BLG in solution determines the magnitude of the electric field at the solution's interface and thereof, a charge reversal can occur when the isoelectric point of BLG moieties (pI ≈ 5.1) is crossed [35].…”
Section: Introductionmentioning
confidence: 99%
“…Zeta-potential analysis again indicated that whey protein, β-lg, gelatine, and lactoferrin electrostatically interact with mucin. [51][52][53][54] However, gelatine and WPI have also been shown to interact with mucin via non-electrostatic mechanisms (Table 1). 55 Evidence supported entropically and enthalpically driven aggregation with formation of hydrogen bonds or hydrophobic interactions even at neutral pH where both whey protein, gelatine and mucins are negatively charged.…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed with WPI, this is likely due to repulsion between β-lg and mucin due both having net negative charges. 43,53 Further, frictional behaviour was dominated by salivary proteins (bovine submaxillary mucin, BSM) 51 rather than by β-lg. With regards to emulsions, at neutral pH, β-lg showed reversible flocculation with…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations